Strategi Memaksimumkan Laba Pada Umkm Central Mainan Anak Tradisional - Amaliyah, Angguliyah Rizqi (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2023)
The implementation of community service activities aims to identify businesses engaged in the craft of traditional children's toys. This activity is useful for improving business understanding in financial management for micro business actors. The method used is to provide education to business owners through training and socialization in financial planning in order to obtain the maximum possible profit. The object of the service activity is one of the traditional children's toy handicraft businesses located in Kepanjen District. During the implementation of the service, we found problems in the field of financial management, namely strategies to increase profits that are still minimal. From these problems, the service team provided education on profit maximization strategies for these UMKM. This education includes the delivery of knowledge on strategies in maximizing profits, training in making financial reports. The results of this service activity are very beneficial for increasing income for UMKM and knowing the importance of strategies or how to calculate good and correct profits.